A Comparative Study of postgraduate Students’ Satisfaction with the Quality of Educational Services in the Syrian Coast - A Field Study in the Faculty of Economics in Tishreen and Tartous Universities) - Mohammad, Osama (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
The aim of this study is to identify the quality of educational services offered by the Faculty of Economics in Tishreen and Tartous Universities from postgraduate students’ point of view, and to determine the level of students’ satisfaction with the educational services provided. The study population consisted of postgraduate students in the Faculty of Economics in both Tishreen and Tartous Universities. The researcher used the analytical descriptive method to measure students’ satisfaction with the quality of educational services provided. A questionnaire was designed and distributed to postgraduate students in order to measure the quality of educational services in both Universities. SPSS was used to study and analyze data. Data analysis showed dissatisfaction with the quality of educational services provided by the Faculty of Economics in Tishreen University, and satisfaction with the quality of the educational services provided by the Faculty of Economics in Tartous University from postgraduate students’ point of view according to the quality dimensions of the educational services (i.e. tangibility, reliability, responsiveness, empathy, trust and safety).